(untitled) (Conference Zone, 2022)
The tasks of education in assisted schools are carried out along with the correction of defects encountered in students with mental retardation. Therefore, one of the main, necessary characteristics of education in auxiliary schools is its orientation to the correction of the defect, and the second characteristic is that it is carried out taking into account the unique characteristics of the development of the mentally retarded student. Deficits in brain activity limit the development of students with mental retardation and cause them to fall behind. Cognitive activity and independence of a mentally retarded student is somewhat lower. This deficiency is manifested when they directly face the difficulties of life.